A simple handbook for academic writing / Jebakumari Selvarani Ebenezer … [et al.] - Ebenezer, Jebakumari Selvarani; Mohaini, Muhammad Luthfi; Asary, Munirah; Zaraini, Noor Shariena; Abdullah, Nor Eleyana; Wan Yadri, Wan Syariza (UiTM Press, 2020)
This book is specially written to guide students on how to write an academic writing paper in an organised way. It provides a step by step method on selecting a topic, outlining, gathering sources, drafting, avoiding plagiarism and lastly editing and proofreading. This book is useful for students wanting to improve their academic writing. Hence, this book is written with the objective of catering to the great demand for good academic writing skills which are crucial to function effectively in studies. This book also broadly covers all aspects of academic writing and is also appropriate for students pursuing courses in writing skills. It guides students to explore academic writing effectively. With "A Simple Handbook for Academic Writing", lecturers and students will be able to acquire the effective way of writing an academic paper using the guidelines given in this book.